Effects of substrate, temperature, salinity, size and transportation on burrowing capacity of juvenile undulated surf clam Paphia undulata. (23rd February 2022) - Zhang, Pengfei; Yongo, Edwine; Feng, Hao; Pan, Shuai; Sun, Anfu; Zhou, Long; Guo, Zhiqiang; Ke, Caihuan
Abstract: The undulated surf clam, Paphia undulata, is cultured and commercially harvested in southern China, providing a source of food and income. This study evaluated the effects of substrate physical properties, temperature, salinity, size and transportation (exposure time and temperature) on the burrowing capacity of juvenile P. undulata to establish suitable conditions for aquaculture purposes. The percentage of burrowing clams and digging index significantly increased with increased substrate water contents, and the highest percentage of burrowing (97.5%) was recorded in mud substrate with 40% water content. However, digging index decreased significantly with increasing substrate sand contents, and the highest and lowest mean index was recorded in substrates with sand contents 0%–20% and 100% respectively. The clams exhibited faster and higher percentage of burrowing at temperatures 20 and 30°C as opposed to 10 and 34°C. The percentage of burrowing was high at salinity levels 20–40 psu compared with 15 psu. In terms of size, percentage of burrowing followed the order 3 < 5 mm < 10 mm < 15 mm < 20 mm, while burrowing time followed the order 20 mm < 15 mm < 10 mm < 5 mm < 3 mm. Clams exposed to air at 24°C for 1.5 h had the highest percentage of burrowing. In conclusion, mud substrate with ≥40% water content at temperature (20–30°C) and salinity (20–40 psu) was appropriate for P. undulata burrowing and may be appropriate for its culture. Moreover, the suitable transportation condition was <24 h at 24 and 28°C. These findings are useful for P. undulata aquaculture.